EFFECTIVE WAYS AND METHODS FOR DEVELOPING INDEPENDENT THINKING SKILLS IN PRIMARY SCHOOL STUDENTS - Murodullayeva Dilsora Ilhom kizi (Western European Studies, 2025)
this article discusses effective methods aimed at developing independent thinking skills in primary school students. Teachers are provided with ways to develop students' thinking using methods such as creating problem situations, question-and-answer, creative tasks, and group work. The article shows effective pedagogical methods aimed at developing students' skills such as expressing their opinions, solving problems, and answering questions.
Keywords: independent thinking; primary school; pedagogical methods